Product Development of Crocodile Jerky - Sinee Nongtaodum; Nongnuch Raksakulthai; Mayuree Chaiyawat (Agriculture and Natural Resources, 2005)
Crocodile jerky was developed from freshwater crocodile (Crocodylus siamensis) tail meat. The Ratio Profile Test (RPT) was used to find the most acceptable product. Seasonings (soy sauce, sugar, and pepper) and processing conditions (drying time and temperature, frying time and temperature) were varied. The jerky sample with 8 % soy sauce, 6.5 % sugar, 2.5 % pepper and 3 % white sesame seed, dried at 60oC for 2 hours and fried at 160oC for 1 minute received the highest acceptability score (P ≤ 0.05). The shear force, L*, a*, b* values and aw of the prepared product were 25.8 N., 41.5, 5.3, 9.4 and 0.63, respectively. The proximate composition of the fresh meat was 72.3 % moisture, 20.2 % protein, 5.5 % fat, 1.0 % ash and 0.9 % carbohydrates, and the total viable bacterial count was 1.48 x 106 CFU/g. The proximate composition of the jerky was 13.9 % moisture, 48.2 % protein, 14.7 % fat, 5.3 % ash and 17.9 % carbohydrates. No microorganism was found in the jerky. The product shelf life was determined according to the thiobarbituric acid number set at 2.5 mg malonaldehyde/Kg by accelerated temperature test. The product was stored in aluminum foil laminated plastic (OPP/LDPE/Al/LDPE/OPP) bags at ambient temperature (30±3oC) under different conditions. The results showed that shelf life was 7 weeks when packed under air, 9 weeks under air with moisture absorber, 14 weeks under air with oxygen absorber and 13 weeks under modified atmosphere of 100 % nitrogen.